Analysis of the length of stay of tourists in Mataram City - Suwardi, Didik; Permata Cita, Fitria; ,, Jumaidin; ., Afifudin (Jurnal Manajemen Pelayanan Hotel, 2024)
West Nusa Tenggara (NTB) Province is one of the provinces in Indonesia which in its development istargeted to become a national tourism gate with other provinces in the Nusa Tenggara region. NTB Provincewith the tagline "Pesona Lombok Sumbawa" has a lot of potential for natural beauty and local culture for localand foreign tourists. Despite the state of NTB tourism which is struggling from the impact of the Lombokearthquake in 2018, the tourism sector by the Tourism Office continues to make efforts to design theimprovement and recovery of the creative industry and tourism in NTB.. The world's growing tourism sectorhas a real impact on economic growth and increased foreign exchange earnings, and Indonesia is no exception.Tourist length of stay is the number of nights or days spent by a foreign tourist outside of his or her country ofresidence). This research aims to find a model to see and measure the level of willingness of tourists to stay ina destination will be interesting and help provide an overview for stakeholders in the tourism industry. So, withthat in mind, this research method uses a quantitative approach, the population and sample in this study were52 respondents with research locations in the city of Mataram. the results of this study indicate that 1) Thelength of stay of Mataram City tourists during 2022 is 0.91 days. This has increased when compared to thelength of stay of tourists in 2021 which is around 0.87 days; 2) The average length of stay of foreign tourists instar hotels is 1.02 days. Meanwhile, the length of stay of domestic tourists in star hotels is 0.84 days; 3) Theaverage length of stay of foreign tourists in non-star hotels is 0.82 days. While the length of stay of domestictourists in non-star hotels is 0.95 days;Keywords: Length of Stay, Tourists, Mataram City